An energy management system enhancement for micro-grid using state-flow - Abderrahmane Ouadi; Abdelkader Zitouni; Hamid Bentarzi (Institute of Advanced Engineering and Science, 2026)
This research focuses on the use of state-flow (SF) technique to enhance the energy management system (EMS) of a smart micro-grid that integrates multiple renewable energy sources. An EMS is responsible for efficiently balancing energy generation and electricity demand by controlling various energy sources, integrating photovoltaic (PV) system as the primary electrical source, batteries, and the utility grid or engine-generator sets as backups. A supervisory control algorithm is implemented within the EMS to optimize power flow among the micro-grid components. In this study, a control system based on the SF technique is designed, implemented, and evaluated under various operational scenarios. The proposed approach is simulated using MATLAB/Simulink and tested under different environmental and load conditions to assess its performance and validate its effectiveness. During testing, the PV system operates as the primary energy source, while the other electrical power sources function as backups. The EMS prioritizes the use of PV panels associated with the battery storage unit for satisfying the load demand. The simulation obtained results demonstrate that the proposed SF-based control approach improves the EMS performance, and hence the overall efficiency, reliability and the stability of smart micro-grid.